Survey of Nunavut Post-Secondary Students: Determinants of School Completion, Post-Secondary Education, and Education Success - Sallaffie, Moriah; Cherba, Maria; Healey Akearok, Gwen K.; Penney, Jessica (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
Little is known about Nunavut students’ experiences in high school and post-secondary education, in particular their self-defined determinants of success. This study aimed to understand factors that influence secondary school completion, post-secondary education, and education success for students from Nunavut. An online survey was conducted with 91 current post-secondary students in 2018–19. Results found that students articulated complex support needs that influence their success, with roles for parents, teachers, and the community. Students identified support needs gaps, primarily in the form of funding distribution and delivery. Recommendations include increased financial, counselling, and mental health support for Nunavut students.